Scientific Opinion on Flavouring Group Evaluation 57, Revision 1 (FGE.57Rev1): consideration of isopulegone and three flavouring substances evaluated by JECFA (55th meeting) - EFSA Panel on Food Contact Materials, Enzymes, Flavourings and Processing Aids (CEF) (EFSA Journal, 2017)
Abstract The EFSA Panel on Food Contact Materials, Enzymes, Flavourings and Processing Aids was requested to consider evaluations of flavouring substances assessed since 2000 by the Joint FAO/WHO Expert Committee on Food Additives (JECFA), and to decide whether further evaluation is necessary, as laid down in Commission Regulation (EC) No 1565/2000. The present consideration concerns a group of four flavouring substances consisting of isopulegone and three other substances evaluated by JECFA at the 55th meeting. This revision is made due to additional toxicity data available for (1R,2S,5R)‐isopulegol [FL‐no: 02.067]. The substances were evaluated through a stepwise approach that integrates information on structure–activity relationships, intake from current uses, toxicological threshold of concern, and available data on metabolism and toxicity. p‐Mentha‐1,4(8)‐dien‐3‐one [FL‐no: 07.127] is no longer supported by the flavour industry and was not evaluated. In agreement with JECFA, the Panel evaluated the candidate substances in this Flavouring Group Evaluation (FGE) via the B‐side of the Procedure. Based on a no observed adverse effect level (NOAEL) from a 90‐day oral toxicity study on [FL‐no: 02.067], adequate margins of safety for the three candidate substances could be calculated. Therefore, the Panel agrees with the JECFA conclusion, ‘No safety concern at estimated levels of intake as flavouring substances’ based on the maximised survey‐derived daily intake (MSDI) approach. Besides the safety assessment of these flavouring substances, the specifications for the materials of commerce have also been considered and found adequate. For the three substances evaluated in this FGE, use levels have become available and the modified theoretical added maximum daily intakes (mTAMDIs) were estimated. For [FL‐no: 02.067 and 07.067], the mTAMDI exceeds the toxicological threshold of concern for their structural classes and need more refined exposure assessment to finalise the evaluation.